Validation and application of an HPLC-UV method for routine therapeutic drug monitoring of dalbavancin - Chiriac, Ute; Rau, Heike; Frey, Otto R.; Röhr, Anka C.; Klein, Sabrina; Meyer, Anna L.; Morath, Benedict (Antibiotics, 2022)
Dalbavancin is emerging as a promising alternative in the ambulant treatment of gram-positive infections that require long-term antibiotic treatment such as osteomyelitis, prosthetic joint infections, and endocarditis. The aim of the current study was to develop and validate a simple, rapid, and cost-effective high-performance liquid chromatography-ultraviolet spectrometry (HPLC-UV) method for the quantification of dalbavancin. Sample clean-up included a protein precipitation protocol, followed by chromatographic separation on a reverse phase HPLC column (C-18) with gradient elution of the mobile phase. Quantification was performed with the internal standard (caffeine) method. Linear relationships between peak area responses and drug concentrations were obtained in the range of 12.5-400 mg/L. The variation coefficient of precision and the bias of accuracy (both inter- and intraday) were less than 10%. The limit of quantification (LOQ) was 12.5 mg/L. The simple and reliable HPLC-UV assay described is a powerful tool for routine therapeutic drug monitoring (TDM) of dalbavancin in human serum in clinical laboratories. With a total process time of approximately 20 min, it allows for accurate and selective quantification up to the expected pharmacokinetic peak concentrations. The method was successfully used to analyze subsequent serum samples of three patients and showed good performance in monitoring serum levels.
Gesehen am 30.06.2022
This article belongs to the special issue "Therapeutic drug monitoring of antimicrobials"